Pengaruh Promosi dan Website Quality Terhadap Impulse Buying Pada E-Commerce Lazada di Kota Padang - Aan Satria; Okki Trinanda (Universitas Negeri Padang, 2019)
The e-commerce business has now developed rapidly, the impact of development is that the number of prosuct varies and easily earned. The ease of such information will result in consumers will be more consumptive infulfilling their needs, even they tend to make impuse buying. As one of the emerest e-commerece in Indonesia, Lazada should be able to see this as a great opportunity in as effort to increase the company’s sales and sustainability. One effort in increasing impulse buying is of external factors ranging from the promotion and quality of websites that are launched on e-commerce bussines. This study aims to know and prove how much influence promotion and website quality to impulse buying e-commerce Lazada in Padang City. The samples were taken using Cochran formula with 100 respondents. This sampling technique is based on nonprobability sampling method. The type of data used in this study is primary data. Data analysis technique used multiple regression analysis technique using SPSS version 20. The results of this study indicate that: (1) Promotion has positive influence and significant effect toward impulse buying e-commerce Lazada in Padang city (0,014 < 0,05). (2) Website Quality has positive influence and significant effect toward impulse buying e-commerce Lazada in Padang city (0,046 < 0,05)Keyword: promotion, website quality, impulse buying.